PERJUANGAN ANGKATAN GERILYA SIPIROK (AGS) DALAM PERANG KEMERDEKAAN DI TAPANULI SELATAN (1949-1950) - Cipto Duwi Priyono (Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to know AGS’s role in the war of independece in South Tapanuli. This research uses history method includes four steps (1): heuristic namely data collection phase, (2) criticism of souece to test source, and (3) interpretation to ininterpret the data, and (4) historiograpy to write data. Based on the data analisys, it can found that AGS was formed january 1 st 1949 and Sahala Muda Pakpahan as the leader. AGS includes TKR, vanguard and ordinary people. Teh battle of AGS was conducted during the second Ducth agression at Tor Simago-Mago. The mago to kill Colonial Army Commander, General Simon Spoor. The result of the agression thet was wants to return control of Indonesian. The role of AGS’s role in the war of Independence of the Republic of Indonesia is immense, especially in breaking the Ducth force form West Sumatra to East Sumatra.